Partisipasi Masyarakat sebagai Faktor Utama dalam Pengembangan Desa Wisata Kaba-Kaba - Darmayanti, Putu Widya; Fila Hidayana, Fransiska; A.A. Sagung Ayu Srikandi Putri; I Wayan Wijayasa (LEMBAGA PENELITIAN DAN PENGABDIAN KEPADA MASYARAKAT AKADEMI PARIWISATA DENPASAR, 2021)
This article examines the factors that motivate the community to support the development of the Kaba-Kaba tourist village. This research used qualitative and quantitative data. Collecting data using questionnaires and in-depth interviews with community leaders. Respondents were determined hundred peoples with proportional random sampling technique. Data analysis used confirmatory factor analysis techniques. The results showed that all factors, both social, cultural, community participation, and environmental factors had a significant effect on community motivation to support the development of tourist village. Statistically, of the 4 factors, the community participation factor is the most dominant, followed by cultural, social, and environmental factors. This means that the community participation factor is the main factor for the community to support the development of tourist village in their village.